Kreatifitas dan Inovasi Dalam Merayakan Peringatan 17 Agustus 2023 Upaya Menumbuhkan Rasa Cinta Tanah Air Bersama Masyarakat Kampung Cilimus Desa Cikande Kecamatan Saguling Kabupaten Bandung Barat - Lathifah, Evi; Safe’i, Abdullah; Prayoga, Adam Raka; Azzahra, Muthia (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
The commemoration of August 17 is a very meaningful moment for all Indonesian people, which also applies to Cilimus Village, Cikande Village, West Bandung Regency. This article is an attempt to explore how the commemoration of August 17 2023 in Cilimus Village reflects a sense of love for the country, at the Religious Moderation Real Work Lecture (KKN) which is one of the activities that must be carried out by all students of Bandung State Islamic University to apply the knowledge they have gained during lectures and as a form of community service. From group 194, the aim of this research was to explore and document the creativity and innovation of the people of Cilimus Village in celebrating the anniversary of 17 August, as well as understanding the positive impact on their sense of love for their country and pride in local culture. The methods applied in this activity were direct observation, interviews with the community, document analysis and a qualitative approach. The results obtained in this 17th activity were Innovation in Commemoration Organizations, Increasing Love for the Motherland, the Role of Traditional Art, Technology and Tradition, national feelings, as well as providing insight into how creativity and innovation can revive national commemorations.